2014
DOI: 10.1111/bor.12066
|View full text |Cite
|
Sign up to set email alerts
|

10Be dating of the Main Terrace level in the Amblève valley (Ardennes, Belgium): new age constraint on the archaeological and palaeontological filling of the Belle‐Roche palaeokarst

Abstract: It is still disputed whether very old archaeological and palaeontological remains found in the Belle-10 Roche palaeocave (eastern Belgium) pertain to the Early (~1 Ma) or Middle (~0.5 Ma) Pleistocene. 11 Here, in situ-produced cosmogenic 10 Be concentrations from a depth profile in nearby sediments of the 12 Belle-Roche terrace (Amblève Main Terrace level) are used as an indirect solution of this 13 chronological issue. The distribution of 10 Be concentrations in the upper 3 m of this profile displays the 14 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 46 publications
0
2
0
4
Order By: Relevance
“…Alternative approaches to dating cave materials, such as cosmogenic burial studies, have demonstrated the Early-Mid Pleistocene to Pliocene antiquity of some cave and palaeokarst systems 3035 , even in regions that clearly are neither arid, nor characterised by low average denudation rates. In addition, the speleothem palaeoclimate literature itself has always included ‘infinite age’ samples – those beyond the reach of the U-Th decay scheme.…”
Section: Remarkable Preservation Of the Nullarbor Cavesmentioning
confidence: 99%
“…Alternative approaches to dating cave materials, such as cosmogenic burial studies, have demonstrated the Early-Mid Pleistocene to Pliocene antiquity of some cave and palaeokarst systems 3035 , even in regions that clearly are neither arid, nor characterised by low average denudation rates. In addition, the speleothem palaeoclimate literature itself has always included ‘infinite age’ samples – those beyond the reach of the U-Th decay scheme.…”
Section: Remarkable Preservation Of the Nullarbor Cavesmentioning
confidence: 99%
“…This debate is all the more relevant when considering the twenty bones suggested to have trace of butchery. While a dozen of these bones were previously considered to have definitive evidence of anthropogenic origin (Cordy et al 1993;Rixhon et al 2014), they were recently revisited with the conclusion that they, in fact, indicate natural actions (Abrams, in litteris). In this respect, the reading of the surface condition of the lithic remains, which constitute the oldest remains found in Belgium and more widely in the Benelux, contributes to this outstanding issue.…”
Section: Introductionmentioning
confidence: 99%
“…Ces résultats ont rapidement été remis en cause et il est proposé que l'âge du « Complexe fluviatile » se situe entre -0,99 et -1,07 Ma ; l'inversion magnétique étant alors corrélée à l'évènement de Jaramillo et non plus à celui de Bruhnes (Renson et al 1997(Renson et al , 1999Juvigné et al 2005). Pour autant, cette attribution est loin de faire l'unanimité et semble dépendre des méthodes et modèles utilisés : géomorphologie et géométrie des terrasses du Bassin de la Meuse, paléomagnétisme, datation absolue par isotopes cosmogéniques (Rixhon et al 2014). Ainsi, Rixhon & Dumoulin (2010) ont proposé de corréler les dépôts du « Complexe fluviatile » à la terrasse de la Belle-Roche, dont le sommet reconnu par sondage affleure seulement trois mètres sous les dépôts de base de la séquence du paléokarst.…”
Section: Introductionunclassified
See 2 more Smart Citations